THE PSYCHOMOTOR PHYSICAL EDUCATION CLASSES IN CHILDREN: A CASE STUDY (Fiep Bulletin - online, 2012)
The present study emphasizes early childhood education and its relationship with the psychomotor elements, as essential components for the development of the child. This work has as main objective to verify if the motor aspects associated with the psychomotor, affective, cognitive and social development is used as a pedagogical tool for teaching, based on the physical education classes. The research was characterized as a case study that proposes a qualitative approach, this way, and field and descriptive. The instruments used for data collection were: open interview with Professor of Physical Education, direct observation, systematic and non-participant. During our observations, it was revealed that the elements are present in psychomotor activities proposed at random, without a specific concern for the teacher, ie, without prior planning. The psychomotor is surrounded by purposes that are relevant in childhood and in the face of experience that should be offered to students, psychomotor elements, you must realize the difficulties, emotions, expressions, they demonstrate to perform the movement.
Keywords: Psychomotor; Physical Education; Early Childhood Education.